A qualitative study of perceived barriers to hepatitis C care among people who did not attend appointments in the non-urban US South - Jacqueline E. Sherbuk; Alexa Tabackman; Kathleen A. McManus; Terry Kemp Knick; Julie Schexnayder; Tabor E. Flickinger; Rebecca Dillingham (BMC, 2020)
Abstract Background Most people diagnosed with hepatitis C virus (HCV) have not linked to care, despite the availability of safe and effective treatment. We aimed to understand why people diagnosed with HCV have not pursued care in the non-urban Southern United States. Methods We conducted a survey and semi-structured interview with participants referred to an HCV clinic who did not attend an appointment between 2014 and 2018. Our clinic is located in a non-urban region of Virginia at a university hospital. Qualitative data collection was guided by the Health Belief Model (HBM). Data was analyzed using qualitative content analysis to identify key factors influencing patient perceptions regarding HCV and pursuit of care. Results Over half of previously referred patients (N = 200) could not be reached by phone. Eleven participants enrolled, including 7 men and 4 women. Based on survey responses, unreliable transportation, unstable housing, substance use, and lack of insurance were common. Participants demonstrated good knowledge of HCV disease, complications, and treatment. On qualitative analysis of semi-structured interviews, final themes emerged from within and between HBM constructs. Emerging themes influencing patient perceptions included (1) structural barriers, (2) stigma, (3) prior experiences of HCV disease and treatment, (4) discordance between the recognized severity of HCV and expected impacts on one's own health, and (5) patient-provider relationship. Substance use was not identified to be a barrier to care. Conclusions Participants perceived individual and structural barriers to linking to care. A strong HCV knowledge base was not sufficient to motivate pursuit of care. Efforts to improve linkage to care must address barriers at multiple levels, and system-level changes are needed. As the majority of previously referred patients could not be contacted by phone, current approaches to patient engagement are not effective for reaching these populations. Expansion of HCV care to primary care settings with an established patient-provider relationship or co-located treatment within substance use treatment programs may serve to increase access to HCV treatment.